Dermatologic care of sexual and gender minority/LGBTQIA youth, Part I: An update for the dermatologist on providing inclusive care. Issue 5 (1st July 2019) - Boos, Markus D.; Yeung, Howa; Inwards‐Breland, David
Abstract: Sexual and gender minority (SGM) persons, including lesbian, gay, bisexual, transgender/gender diverse, questioning/queer, intersex, and asexual (LGBTQIA) individuals, represent a historically underserved population within the field of medicine, though their unique health needs are increasingly recognized. Unfortunately, our understanding of these needs as they relate to dermatology is still nascent, particularly with respect to children and adolescents. This two‐part review will discuss the dermatologic care of SGM youth, with Part 1 providing practical advice for dermatologists seeking to provide more culturally mindful and accessible care for SGM children and adolescents. A more comprehensive understanding of the psychosocial and physical needs of SGM youth will allow dermatologists to more actively and compassionately care for this health disparity population.